Grassroots Organizing in the Digital Age: Considering Values and Technology Decision-making in Tea Party and Occupy Wall Street - Agarwal, Sheetal D; Johnson, Courtney N; Bennett, W. Lance; Borning, Alan (AoIR Selected Papers of Internet Research, 2013)
Technology both supports and constrains different types of behavior, and so decision to employ a specific technology within a community is important as users may resist or adopt use of the technology based on these traits. In this study we explore the values, attitudes, and beliefs of Tea Party and Occupy Wall Street stakeholders as they relate to their use of technology. We employ Value Sensitive Design to examine stakeholder values, and potential sites of value tensions we use semi-structured interviews conducted with three distinct groups of stakeholders in Tea Party and Occupy: members with some type of leadership or facilitator position, technologists, and lay members. This study provides insight into the potentially complex decision-making processes involved in the adoption of technology within grassroots social movements, as well as any ongoing struggles movement leaders and members face as they try to sustain involvement using whatever tools are at their disposal.